2012
DOI: 10.1002/pd.3837
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of cardiac defects: accuracy and benefit

Abstract: Prenatal diagnosis was accurate and the counselling appropriate in most cases; however, a few errors were made. The diagnosis of aortic coarctation remains challenging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 33 publications
(56 reference statements)
3
21
0
Order By: Relevance
“…Our overall mortality rate was 6.6% which correlates well with recent data ranging between 6.5 and 8.7% [32,33], and considerably lower than the 11-16% reported [34,35]. This rate was very low for simple TGA (1.9%) compared to recent studies showing mortality rates between 3.7 and 12.7% [7,35].…”
Section: Discussionsupporting
confidence: 70%
“…Our overall mortality rate was 6.6% which correlates well with recent data ranging between 6.5 and 8.7% [32,33], and considerably lower than the 11-16% reported [34,35]. This rate was very low for simple TGA (1.9%) compared to recent studies showing mortality rates between 3.7 and 12.7% [7,35].…”
Section: Discussionsupporting
confidence: 70%
“…Studies of the correlation between prenatal ultrasound scans and pathology examinations show that diagnostic misclassifications principally concern heart disease [18,19,21], with the most frequent diagnostic error that of a ventricular septal defect, which often marks valvular disease [19,39]. Similarly, it has already been shown that postnatal pathology examinations fail to confirm a substantial portion of cerebral malformations [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings, however, do support the continued practice of referring pregnancies with enlarged NT measurements for a fetal echocardiogram because of the substantially better prenatal detection of CCHDs with referral. 40 If such screening is done for aneuploidy detection or early anatomy screening, a CRL-specific 99th percentile cutoff appears to out-perform the currently used cutoff of 3.5 mm in the identification of pregnancies that are at increased risk for CCHDs. In millimeters, by percentile and 3.5 mm cutpoints in the detection of critical congenital heart defects that occur without chromosomal defects.…”
Section: Obstetrics Researchmentioning
confidence: 99%